Transplantation to study satellite cell heterogeneity in skeletal muscle - Hekmatnejad, Bahareh; Rudnicki, Michael A. (Frontiers in Cell and Developmental Biology, 2022)
Skeletal muscle is characterized by a remarkable regenerative capacity mediated by tissue-specific muscle stem cells, also called satellite cells. Satellite cells, located peripheral to the muscle fiber but under its basal lamina, are an indispensable cellular source for muscle regeneration. Transplantation of satellite cells into mammalian skeletal muscle provided the first evidence that satellite cells function as adult muscle stem cells. Moreover, satellite cells are a heterogenous population in adult tissue, with subpopulations which can be distinguished based on gene expression, cell-cycle progression, ability to self-renew, and bi-potential ability. Transplantation assays provide a powerful tool to better understand satellite cell function in vivo enabling the separation of functionally distinct satellite cell subpopulations. In this review, we focus on transplantation strategies to explore satellite cells functional heterogeneity, approaches targeting the recipient tissue to improve transplantation efficiency, and common strategies to monitor the behaviour of the transplanted cells. Lastly, we discuss some recent approaches to overcome challenges to enhance the transplantation potential of muscle stem cells.